Relationship Of Brushing Teeth Skills With Debris Index In The Older Adults At Tambak Wedi Baru Surabaya - Prasetyowati, Silvia; Kinzoku Nur Alif; Bambang Hadi Sugito; Isnanto (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
The proportion of Indonesians who have dental and oral problems at the age of 55-64 years is 61.9% and the age of >65 years is 54.2%. As well as the proportion of daily brushing behaviour, namely 94.7% and 2.8% have brushed their teeth twice a day. The problem of this study is the high prevalence of debris index in older adults in Tambak Wedi Baru Surabaya. The purpose of the study was to find out the relationship between of knowledge how to brush teeth and debris index in the older adults at Tambak Wedi Baru Surabaya. The type of research is cross-sectional with the number of respondents being 50 older adults. Research method by filling out observation sheets. The data analysis technique used is by tapping the results of data that has been collected and presented in the form of tables. The results showed that there is a relationship between knowing how to brush teeth with dental hygiene in older adults.